Evidence from a Series of 104 Equine Sarcoids Suggests That Most Sarcoids in New Zealand Are Caused by Bovine Papillomavirus Type 2, although Both BPV1 and BPV2 DNA Are Detectable in around 10% of Sarcoids - Munday JS; Orbell G; Fairley RA; Hardcastle M; Vaatstra B (MDPI (Basel, Switzerand), 2021)
Equine sarcoids are common mesenchymal neoplasms of horses that are caused by cross-species infection by deltapapillomaviruses. While bovine papillomavirus (BPV) 1 and 2 are the most common causes, there are differences between countries regarding which of these BPV types cause the majority of sarcoids. Additionally, no causative PV can be detected in a subset of sarcoids, suggesting that other PV types could be rarer causes of these neoplasms. In the present study, consensus PCR primers and PCR primers specific for the five deltapapillomavirus types currently known to cause mesenchymal neoplasia (BPV1, BPV2, BPV13, BPV14, and Ovis aries PV2 DNA) were used to investigate the presence of PV DNA in 104 sarcoids from three defined regions in New Zealand and from two distinct time periods separated by 15 years. PV DNA was detected in 94 (90.4%) sarcoids. Of the sarcoids containing PV DNA, 83 (88.3%) contained only BPV2 DNA, 9 (9.6%) BPV1 and BPV2 DNA, and 2 (2.1%) only BPV1 DNA. No other PV types were detected. The predominance of BPV2 is consistent with studies of sarcoids from North America but dissimilar to studies of sarcoids from Europe and Australia. Detection rates of BPV1 and BPV2 were similar in sarcoids from different regions of New Zealand and in sarcoids from different time periods. These results suggest that most equine sarcoids in New Zealand are caused by BPV2 and thus if vaccines are developed to prevent sarcoids, vaccines that provide good protection against BPV2 will be required in this country.
Keywords: New Zealand; bovine papillomavirus; deltapapillomavirus; horse; neoplasia; sarcoid; skin; vaccine; viral carcinogenesis; viral trends